Essential Oil Composition of Aerial Parts of Two Salvia L. (S. russellii Bentham and S. bracteata Banks & Sol.) Species - Dogan, Gulden; Demirpolat, Azize; Bagci, Eyup (Asian Journal of Chemistry, 2014)
In this Study, essential oil composition of the aerial parts of two Salvia L. (Salvia russellii Bentham and Salvia bracteata Banks & Sol.) I from EastAnatolian region of Turkey were analyzed by GC and GC-MS system. The essential oils of the aerial parts of two Salvia L. (S. russellii and S. bracteata) collected from the Turkey were obtained by hydrodistillation, in 0.8% (v/w) anc10.7 (v/w) oil yields, respectively. Thirty two and fifty five components were identified representing 98.5 and 91 % of the oils; respectively. The major constituents of S. Il russe lu were thymor(31.9 %) okerpinol (13.1 %)', gamma-terpinene (12.5 %), whereas those S. bructeata were caryophYllene oxide (17.8 %), beta-caryophyllene (16.7 %) and beta-pinene (10.5 %).
Keywords: Salvia; Lamiaceae; GC-MS; Essential oil; Chemotaxonomy